2015
DOI: 10.1007/978-3-319-16640-7_4
|View full text |Cite
|
Sign up to set email alerts
|

Culture Systems Incorporating Heterotrophic Metabolism for Biodiesel Oil Production by Microalgae

Abstract: The feasibility of using various culture systems incorporating heterotrophic metabolism for biodiesel oil production was compared. Heterotrophic culture can be used to achieve high cell concentration, and depending on the strain and organic carbon source employed, the introduction of light (mixotrophic culture) can enhance cell growth and oil accumulation. However, mixotrophic cultures also face the problem of light limitation, and depending on the relative concentrations of the organic carbon source and light… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
11
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 62 publications
2
11
0
Order By: Relevance
“…Lipid accumulation was not dependent on the initial medium glycerol contents in the present study. In the heterotrophic cultivation of algae for lipids, it has been reported that increasing the carbon substrates concentrations leads to increase in lipid accumulation [9] [10]. In the present study, lipid accumulation seemed to be uniform irrespective of the initial medium glycerol level.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…Lipid accumulation was not dependent on the initial medium glycerol contents in the present study. In the heterotrophic cultivation of algae for lipids, it has been reported that increasing the carbon substrates concentrations leads to increase in lipid accumulation [9] [10]. In the present study, lipid accumulation seemed to be uniform irrespective of the initial medium glycerol level.…”
Section: Discussionsupporting
confidence: 55%
“…Not all oils are suitable for biodiesel production de novo. Ogbonna and McHenry [9] and Ogbonna and Moheimani [10] reported that oil quality of heterotrophically cultivated algal cells is better than those under photoautotrophic…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, lipid accumulation in heterotrophic cultures was significantly higher than the values obtained in photoautotrophic cultures. This also supports dome previous reports[9] [12][13] [14]…”
supporting
confidence: 92%
“…[10] [11] [14] [15] [34]. Similarly, lipid accumulation in heterotrophic cultures was significantly higher than the values obtained in photoautotrophic cultures.…”
mentioning
confidence: 71%
“…There are many benefits of heterotrophic/mixotrophic cultures over photoautotrophic cultures. These include the use conventional bioreactors which are simpler and easier to scale up, elimination of light requirements, higher cell densities, which reduce the cost of harvesting the cells (Ogbonna and McHenry 2015). Owing due to requirement of low light intensity, some mixotrophic strains have reduced photoinhibition and growth rates are higher as compared to photoautotrophic and heterotrophic Pahl et al (2013)] cultures.…”
Section: Heterotrophic/mixotrophic Cultivationmentioning
confidence: 98%